Ruthenium-nickel heterobimetallic complex as a bifunctional catalyst for ROMP of norbornene and ethylene polymerization - Masson, Gustavo H. C. [UNESP]; Cruz, Thaís R. [UNESP]; Gois, Patrik D. S. [UNESP]; Martins, Daniele M.; Lima-Neto, Benedito S.; Oliveira, Guedmiller S.; Machado, Antonio E. H.; Bernardo-Gusmão, Katia; Goi, Beatriz E. [UNESP]; Carvalho-Jr, Valdemiro P. [UNESP] (Royal Society of Chemistry (RSC), 2021)
Monometallic [RuCl2(η6-p-cymene)(pipNH2)] (mono-Ru) and heterobimetallic [RuCl2(η6-p-cymene)][(μ-Schiff-pip)Ni(PPh3)Cl] (Ru-Ni) complexes were successfully synthesized. They were fully characterized by FTIR, UV-Vis, and NMR spectroscopic studies, elemental analysis, cyclic voltammetry and computational studies. ComplexRu-Niwas additionally characterized by MALDI-TOF mass spectrometry. The polynorbornene (polyNBE) synthesesviaROMP usingmono-RuandRu-Nias pre-catalysts in the presence of ethyl diazoacetate (EDA) were evaluated at different [EDA]/[Ru] ratios, time periods (5-60 min) and temperatures (25 and 50 °C). Higher yields of polyNBE were obtained using [NBE]/[Ru] = 5000 and 5 μL of EDA at 50 °C for 60 min. Under these conditions,mono-Ruexhibited higher catalytic activity thanRu-Ni, reaching 50 and 40% yield, respectively. Hence, a strong steric influence ofRu-Nion the catalytic activity was demonstrated. The order of magnitude of 105g mol−1was measured by SEC forMnandĐvalues ranging from 1.64 to 3.70 formono-Ruand from 1.26 to 2.40 forRu-Ni. The catalytic activity ofRu-Nion ethylene polymerization was evaluated at different [Al]/[Ni] ratios, temperatures (20-60 °C) and reaction times (3-12 h) using MAO as the co-catalyst.Ru-Niwas able to provide an activity of 71.40 kg PE (mol Ni)−1h−1at 40 °C after 3 h in a [Al]/[Ni] molar ratio of 2100, 7 μmol of catalyst in 25 mL of toluene and 116 psi ethylene pressure.